EDUCATION A PESANTREN BASED CURRICULUM DEVELOPMENT MODEL FOR ISLAMIC RELIGIOUS: A CASE STUDY AT MI AL-AZHAR MENGANTI - Barudin; Mulyadi (Makkah: Journal Of Islamic Studies, 2026)
This study aims to analyze the curriculum development model of Islamic Religious Education (PAI) in a pesantren-based madrasah and to identify the gap between the ideal curriculum model and pedagogical reality in the field. A qualitative case study approach was employed at MI Al-Azhar Menganti, Gresik, which operates under the Darul Ihsan Islamic Boarding School Foundation. Data were collected through semi-structured interviews with the Curriculum Coordinator and Deputy Coordinator, then analyzed thematically and mapped onto three curriculum development models: the Tyler model, the Taba model, and the Grass Roots model. The findings indicate that the development of the PAI curriculum in this madrasah follows a hybrid pattern: the curriculum structure is top-down, following Tyler's logic and referring to the Merdeka Curriculum and the Minister of Religious Affairs Decree; pesantren-based content such as Qur'anic reading and writing, akhlak (morals), and ubudiyah (worship practices) reflects the spirit of the Grass Roots model, while a systematic student-needs diagnosis in the manner of Taba has not yet been formally institutionalized. The most prominent gap was found in the utilization of technology and artificial intelligence (AI), which teachers have begun to explore informally but which remains constrained by limited internet infrastructure, uneven digital competence among senior teachers, and pesantren concerns over the displacement of talaqqi (direct teacher-student transmission of values). The study recommends strengthening annual needs-diagnosis mechanisms, developing a gradual AI-integration roadmap, providing differentiated digital-literacy training, and systematically documenting curriculum evaluation on an ongoing basis.